Dynamics of a Diffusive HBV Infection Model with Capsids, Two Delays, and Cell-to-Cell Transmissions - Hui Miao; Meiyan Jiao (Discrete Dynamics in Nature and Society)
This article aims to study a hepatitis B virus (HBV) infection model incorporating two nonlinear incidences and spatial diffusion in capsids, virus, and cytotoxic T lymphocyte (CTL) immune response. Three equilibria which are infection-free, immune-free, and infection with CTL immunity are calculated under rational assumptions. Furthermore, two reproduction numbers are verified to assert the global stability of the HBV model. In the end, the theoretical results on HBV dynamics are further illustrated by performing numerical simulations.